2004
DOI: 10.1042/bj20040198
|View full text |Cite
|
Sign up to set email alerts
|

Getting into position: the catalytic mechanisms of protein ubiquitylation

Abstract: The role of protein ubiquitylation in the control of diverse cellular pathways has recently gained widespread attention. Ubiquitylation not only directs the targeted destruction of tagged proteins by the 26 S proteasome, but it also modulates protein activities, protein-protein interactions and subcellular localization. An understanding of the components involved in protein ubiquitylation (E1s, E2s and E3s) is essential to understand how specificity and regulation are conferred upon these pathways. Much of wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
212
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(223 citation statements)
references
References 167 publications
3
212
0
6
Order By: Relevance
“…Moreover, we found that the genes related to E3 ubiquitin ligase were up-regulated in BAT of the fasted rats (Table 5). E3 ubiquitin ligase is considered to determine the substrate specificity for protein ubiquitination, 28,29) and the result suggests that there are potential target proteins for ubiquitination other than ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the genes related to E3 ubiquitin ligase were up-regulated in BAT of the fasted rats (Table 5). E3 ubiquitin ligase is considered to determine the substrate specificity for protein ubiquitination, 28,29) and the result suggests that there are potential target proteins for ubiquitination other than ACC.…”
Section: Discussionmentioning
confidence: 99%
“…The ligase specifically recognizes the substrate protein and transfers ubiquitin to the target protein. 18 Subsequently, the target proteins are unfolded and degraded by an ATP-dependent process. 19 Two muscle-specific E3 ubiquitin ligases named muscle atrophy Fbox (MAFbx, atrogin-1) and muscle RING finger-1 (MuRF-1) were first described in 2001 and are significantly up-regulated during muscle atrophy.…”
Section: Current Developments On Muscle Mass Lossmentioning
confidence: 99%
“…Ubiquitin is then transferred to ubiquitin-conjugating enzymes (E2s) as a thioester. Ubiquitin ligases (E3s) facilitate the attachment of ubiquitin to -amino groups of lysines and, rarely, to the N-terminal amino group in substrates (1,(3)(4)(5)(6). HECT (homology to E6AP C terminus) domain-containing E3s form intermediate thioesters with ubiquitin at their active-site cysteines before transferring the ubiquitin to substrates (3,4,7).…”
mentioning
confidence: 99%
“…Ubiquitination is catalyzed by a cascade of enzymes (1,3,4). The active-site cysteine of ubiquitin-activating enzyme (E1) forms a thioester with ubiquitin in an ATP-dependent reaction.…”
mentioning
confidence: 99%